Normal mode of dc discharge in argon, hydrogen and oxygen - Lisovskiy, V.A.; Artushenko, K.P.; Yegorenkov, V.D. (Вопросы атомной науки и техники, 2016)
This paper reports the current-voltage characteristics and the j/p²similarity parameter determination in argon, hydrogen and oxygen in the pressure range from 0.1 to 10 Torr. Experiments have been performed in the discharge tube of 56 mm inner diameter and with stainless steel electrodes. Anode diameter was 55 mm whereas the diameters of the cathodes employed were 55 and 12 mm. The j/² parameter has been shown to remain constant only at the gas pressure above 1 Torr. Its values comprise j/p²= (0.092 ±0.02) mA/(cm² ∙Torr² ) for argon, j/p²= (0.072 ±0.02) mA/(cm² ∙Torr² ) for hydrogen and j/p ² = (0.33 ±0.05) mA/(cm² ∙Torr² ) for oxygen. On lowering the pressure (below 1 Torr) the j/p²parameter grows fast and at the pressure of 0.1 Torr it may be two orders of magnitude higher than one at 1 Torr. Были измерены вольт-амперные характеристики и определены величины параметра подобия j/p² в аргоне, водороде и кислороде в диапазоне давлений газа 0,1…10 Торр. Эксперименты проведены в разрядной трубке с внутренним диаметром 56 мм и электродами из нержавеющей стали. Диаметр анода был 55 мм, в то время как диаметры используемых катодов были равны 55 и 12 мм. Показано, что j/p ²сохраняется постоянным только при давлениях газа выше 1 Торр. При этом j/p 2 = (0,092 ±0,02) мА/(cм² ∙Toрр²) для аргона, j/p² = (0,072 ±0,02) мA/(cм² ∙Toрр²) для водорода и j/p² = (0,33 ±0,05) мA/(cм²∙Toрр² ) для кислорода. При понижении давления (ниже 1 Toрр) j/p² быстро возрастает, и при давлении 0,1 Toрр j/p² может быть на два порядка выше, чем при 1 Toрр. Були виміряні вольт-амперні характеристики та визначено величини параметра подібності j/p² в аргоні, водні та кисні в діапазоні тиску газу 0,1…10 Торр. Експерименти проведені в розрядної трубці з внутрішнім діаметром 56 мм і електродами з нержавіючої сталі. Діаметр анода був 55 мм, в той час як діаметри катодів, що використовуються, були рівні 55 і 12 мм. Показано, що j/p 2 зберігається постійним тільки при тиску газу вище 1 Торр. При цьому j/p² = (0,092 ±0,02) мА/( cм²∙Toрр²) для аргону, j/p² = (0,072 ±0,02) мA/( cм²∙Toрр²) для водню j/p² = (0,33 ±0,05) мA/(cм² ∙Toрр² ) для кисню. При зниженні тиску (нижче 1 Toрр) j/p² швидко зростає, і при тиску 0,1 Toрр j/p² може бути на два порядки вище, ніж при 1 Toрр.
Нормальний режим тліючого розряду в аргоні, водні та кисні.